2013
DOI: 10.1530/rep-12-0389
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor-α is the signal induced by mating to shutdown a 2-methoxyestradiol nongenomic action necessary to accelerate oviductal egg transport in the rat

Abstract: Mating shut down a 2-methoxyestradiol (2ME) nongenomic action necessary to accelerate egg transport in the rat oviduct. Herein, we investigated whether tumour necrosis factor-α (TNF-α) participates in this mating effect. In unmated and mated rats, we determined the concentration of TNF-α in the oviductal fluid and the level of the mRNA for Tnf-a (Tnf) and their receptors Tnfrsf1a and Tnfrsf1b in the oviduct tissues. The distribution of the TNFRSF1A and TNFRSF1B proteins in the oviduct of unmated and mated was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 43 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…Neutralization of TGFβ1 did not mimic the effect of mating on the non‐genomic 2ME activity, consistent with our previous findings that 2ME does not accelerate egg transport in mated rats (Parada‐Bustamante et al, 2007, 2010). Previously, we showed that TNF‐α participates in the repression of the 2ME effect induced by mating (Oróstica et al, ), so mating appears to differentially regulate the role of cytokines like TNF‐α and TGFβ in the rat oviduct. We cannot, however, exclude the involvement of the TGFβ system in this effect because other components of TGFβ signaling were not assessed in this work; indeed, changes in prolactin secretion, immunomodulation of the genital tract, and/or embryo development may be affected by the decrease in circulating TGFβ1 levels induced by mating (reviewed in Erskine, ; Robertson, ; Orihuela et al, ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Neutralization of TGFβ1 did not mimic the effect of mating on the non‐genomic 2ME activity, consistent with our previous findings that 2ME does not accelerate egg transport in mated rats (Parada‐Bustamante et al, 2007, 2010). Previously, we showed that TNF‐α participates in the repression of the 2ME effect induced by mating (Oróstica et al, ), so mating appears to differentially regulate the role of cytokines like TNF‐α and TGFβ in the rat oviduct. We cannot, however, exclude the involvement of the TGFβ system in this effect because other components of TGFβ signaling were not assessed in this work; indeed, changes in prolactin secretion, immunomodulation of the genital tract, and/or embryo development may be affected by the decrease in circulating TGFβ1 levels induced by mating (reviewed in Erskine, ; Robertson, ; Orihuela et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…Females were used after showing two consecutive 4‐day cycles. The procedure to obtain unmated and mated rats was previously described by Oróstica et al (). Briefly, females at 0:00 hr on Day 1 of the oestrous cycle were either kept isolated or caged with fertile males for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we reported that mating regulates oviductal egg transport (Forcelledo et al 1981), oestradiol (E 2 ) metabolism (Parada-Bustamante et al 2007) and changes in the mechanism by which E 2 accelerates oviductal egg transport (Orihuela et al 2001, Parada-Bustamante et al 2010. Regarding the effect of E 2 on oviductal egg transport, we report that this mating effect is mediated by the cytokine TNF (Orostica et al 2013). Interestingly, mating transiently increased the levels of TNF in the oviductal fluid at 3 h poststimulus; moreover, the oviductal epithelium expresses the TNF receptors TNFRA and TNFRB on its luminal face (Orostica et al 2013).…”
Section: Introductionmentioning
confidence: 90%
“…Cytokines modulate COMT activity in many organs, including the brain, placenta, and uterus (Wentz et al, ; Tchivileva et al, ; Das, ). Oróstica et al () showed that mating increases TNFα abundance in the oviduct fluid, and that administering this cytokine into the oviduct of cycling rats mimicked the effect of mating, accelerating E 2 ‐induced egg transport. Mating decreased TGFβ1 concentration in the plasma but not the oviduct fluid; however, neutralization of circulating TGFβ1 did not prevent the effect of E 2 on egg transport (Oróstica et al, ).…”
Section: Mating Inhibits the Non‐genomic E2 Pathway In The Oviduct Thmentioning
confidence: 99%